Effect of the Microstructures Formed in Cements Modified by Limestone Agave Bagasse Ash, Fly Ash, Geothermal Nano-SiO2 Waste and Silica Fume on Chloride Ion Penetration Resistance - Puente Ornelas, Rodrigo; Chávez Guerrero, Leonardo; Fajardo San Miguel, Gerardo; Rodríguez, E. A.; Trujillo Álvarez, Alejandro; Rivas Lozano, Hugo E.; Delgadillo Guerra, Herlinda María (Electrochemical Science Group, 2016)
In the present work, pastes were fabricated replacing the ordinary portland cement (OPC) by 0, 1.67, 2.5 and 5 wt% of limestone from agave bagasse ash (ABA), fly ash (FA), geothermal nano-SiO2 waste (GNW) and silica fume (SF), using 1.5 wt% of superplasticizer based in carboxylate and a water/binder ratio of 0.45. After fabrication, the pastes were cured at 20ºC and a humidity content of 100% for up to 28 days. The compressive strength, chloride penetration, porosity and microstructural evolution properties were evaluated. The results obtained from the test suggests that the mechanical, electrochemical, physical and microstructural properties resulting from the cured specimens were enhanced, when compared to the cements obtained with pastes composed by 100% of OPC. It was found that the ABA pastes improved by ~15% to ~25% their mechanical resistance, compared with the values obtained for 100% OPC and 5% FA respectively. Additionally, the pastes containing 2.5% of ABA and 2.5% of GNW, showed an increase of 35% in the values of mechanical resistance in comparison to the 100% OPC. It is also worth mentioning that a the pastes experienced a higher densification value, mainly due to the addition of GNW, which promotes the development of a matrix with reduced porosity when compared with values measured at 100% OPC. The chlorine ion penetration ratio had also low values giving an ion penetration resistance around 57 % less. These results revealed that geothermal nano-SiO2 waste (GNW) and limestone of agave bagasse ash (ABA) could be considered as a potentially suitable material for making pastes, mortars and concrete for industrial applications, which will contribute positively to the reduction of the CO2 emissions into the atmosphere, as well as decrease the environmental impact generated at the disposal zones.